THE OEM - OBM DEBATE: FACTORS INFLUENCING CHIN ESE FIRMS' BRANDING DECISIONS IN THEIR INTERNATIONALISATION PROCESS - Ian Wilson (Global Economic Observer)
A key international marketing decision for many Chinese (and firms from other emerging markets) is whether to internationalise their own brands-labelled by the Chinese as OBM (Original or Own Brand Manufacturing)-or to be international players by acting as contract manufacturers(labelled by the Chinese as OEM (Original Equipment Manufacturing) for foreign brand owners(FBOs). The paper discusses some of the extant research on the advantages and disadvantages of each business model and then focuses on primary research conducted amongst 8 Chinese firms in electronics and textiles and the OEM-OBM decisions they face. In so doing, it discusses some of thefactors influencing such decisions and proposes a framework for reviewing them as firm and environmental circumstances change.